THE TRANSFORMATION OF TORAJA ORNAMENT’S MEANING ON DHARMAWANGSA SQUARE TATOR CAFÉ APPLYING HERMENEUTIC THEORY - Lily Wijayanti; I Gede Mugi Raharja; Ida Ayu Dyah Maharani; I Made Pande Artadi (International Journal of Social Science, 2025)
This research aims to analyze the transformation of the meaning of Toraja ornament, particularly, Pa’ Barre Allo motive, using Jakarta Dharmawangsa Tator café Square as the primary data. This study employs Hermeneutics theory by Paul Ricoeur stating that it explains about the rules of the interpretation of texts, signs, and symbols. Moreover, this research discusses about how the traditional Toraja ornament is applied in modern commercial space. Toraja ornament, having sacred meaning traditionally, shifts its meaning as it is implemented in café interior elements of the public spaces. It means that the ornament does not only function as aesthetic elements, but it also has great values, representing the sensibility of Toraja culture on commercial interior design. Furthermore, this study reveals about the application of Pa’ Barre Allo motive on café Tator transforming its sacred meaning to aesthetic elements in order to strengthen the attraction and brand identity of the space of the café. The results of this research are expected to enhance the comprehension of the transformation of the cultural values in commercial interior design. Finally, they can contribute to the preservation of Indonesian history and culture